The Correlation among the Students’ Learning Environment, Personality, and Their Vocabulary Achievement - Julianti Sapta Nadilla; Baso Jabu; Andi Anto Patak (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research was aimed at finding out the correlation between students’ learning environment and their vocabulary achievement, the correlation between students’ personality and their vocabulary achievement and the correlation among students’ learning environment, students’ personality and their vocabulary achievement. To achieve the objectives, the researcher used correlational research and the participants of this study were 30 students who were taken by purposive random sampling technique. The result of this research was gathered by two kinds of questionnaires and a vocabulary test using CEFR level test. The result of this research showed that their learning environment were very good classification, and for the personality of the students were extraversion and openness meanwhile for their vocabulary achievement was mostly in level B1. The result of the correlation between the three variables found that there was a negative correlation between students’ learning environment and their vocabulary achievement as the correlation between them was -0.38. meanwhile, there was low correlation between students’ personality and their vocabulary achievement as the correlation between them was 0.085 as interpreted low category and the correlation among students’ vocabulary achievement, students’ personality and their vocabulary achievement also found no significant correlation as the correlation was 0.149 which interpreted into negligible. It can be concluded that learning environment and personality do not affect students’ vocabulary achievement since there are others factor can influence student learning achievement especially their vocabulary achievement.